EduRoSC-Prof: Continuous Education Method for Teacher Formation in Educational Robotics for K-12 Teaching - Oliveira, Denilton Silveira; Curvelo, Carla Da Costa Fernandes; Melo, Julio C. P.; Santana, Orivaldo Vieira de; Barrios-Aranibar, Dennis; Patino-Escarcina, Raquel Esperanza; Garcia, Luciane Terra Dos Santos; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2021: Anais do XIII Simpósio Brasileiro de Robótica e XVIII Simpósio Latino Americano de Robótica, 2021)
This paper proposes a methodological approach to continuum formation in Educational Robotics including a course approach and a standard curriculum to be used for training teachers of the K-12 system. This paper extends the EduRoSC-Kids as proposed previously, in order for providing teachers with a broader knowledge about the basic knowledge in Robotics and in Educational Robotics. The curriculum takes into account only the strict necessary contents for the teachers training considering that they are of cross disciplines as Physical Education, Biology, Mathematics, Portuguese, Geography, History, Arts, Sociology and Philosophy. These knowledge have proven to be enough, and further used in order to improve their students learning skills. The complete methodology has been successfully applied in the basic public educational system at Natal, in the Brazil Northeast, and in Arequipa, Perú, and has has proven to be a useful tool to help in the learning process.